Mechanism of tacrolimus in the treatment of lupus nephritis - Wang, Ming; Zhou, Jing; Niu, Qiyan; Wang, Hongyue (Frontiers in Pharmacology, 2024)
Systemic lupus erythematosus (SLE) is a complex autoimmune disorder, with more than half of the patients developing lupus nephritis (LN), which significantly contributes to chronic kidney disease (CKD) and end-stage renal disease (ESRD). The treatment of lupus nephritis has always been challenging. Tacrolimus (TAC), an effective immunosuppressant, has been increasingly used in the treatment of LN in recent years. This review aims to explore the mechanisms of action of tacrolimus in treating LN. Firstly, we briefly introduce the pharmacological properties of tacrolimus, including its role as a calcineurin (CaN) inhibitor, exerting immunosuppressive effects by inhibiting T cell activation and cytokine production. Subsequently, we focus on various other immunomodulatory mechanisms of tacrolimus in LN therapy, including its effects on T cells, B cells, and immune cells in kidney. Particularly, we emphasize tacrolimus’ regulatory effect on inflammatory mediators and its importance in modulating the Th1/Th2 and Th17/Treg balance. Additionally, we review its effects on actin cytoskeleton, angiotensin II (Ang II)-specific vascular contraction, and P-glycoprotein activity, summarizing its impacts on non-immune mechanisms. Finally, we summarize the efficacy and safety of tacrolimus in clinical studies and trials. Although some studies have shown significant efficacy of tacrolimus in treating LN, its safety remains a challenge. We outline the potential adverse reactions of long-term tacrolimus use and provide suggestions on effectively monitoring and managing these adverse reactions in clinical practice. In general, tacrolimus, as a novel immunosuppressant, holds promising prospects for treating LN. Of course, further research is needed to better understand its therapeutic mechanisms and ensure its safety and efficacy in clinical practice.